Mohamad Mohsin pioneers Permula Siswa UMPSA Company - Amira Wayhida Izzati, Mohamad Amin; Halizan, Mohmood (UMPSA, 2024)
GAMBANG, 13 March 2024 - A Bachelor of Computer Science (Software Engineering) with Honours 4th year student, Faculty of Computing (FK), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), Mohamad Mohsin Ismail became a pioneer for Permula Siswa Company by engaging in information technology-focused business.